Cover, Content, and Editorial Note from Borneo J Pharm Vol. 5 No. 1 February 2022 - Chief Editor of Borneo J Pharm (Borneo Journal of Pharmacy, 2022)
Assalamu’alaikum Wr. Wb. Alhamdulillahirabbil ‘alamin. The next edition of the Borneo Journal of Pharmacy (Borneo J Pharm), has been published in February 2022. This edition contains ten articles consisting of Pharmacognosy-Phytochemistry, Clinical-Community Pharmacy, Pharmaceutical, Microbiology Pharmacy, and Natural Product Development. This edition includes writings from three countries including Azerbaijan, Indonesia, and Ukraine. The authors come from several institutions, including Universitas Lambung Mangkurat, Universitas Pancasila, Bunda Mother and Child Hospital Jakarta, National University of Pharmacy, Kharkiv National University of Radio Electronics, Universitas Jenderal Achmad Yani, Institut Teknologi Bandung, Universitas Tanjungpura, Universitas Muhammadiyah Kalimantan Timur, Sekolah Tinggi Ilmu Farmasi Makassar, Universitas Gadjah Mada, Universitas Airlangga, and Azerbaijan Medical University. Editorial boards are fully aware that there is still room for improvement in this edition, hence with all humility willing to accept constructive suggestions and feedback for improvements to the publication for the next editions. The editorial board would like to thank all editors and reviewers, and contributors of the scientific articles who have provided the repertoire in this issue. We hope that all parties, especially the contributors, could re-participate for publication in the next edition in May 2022. Wassalamu’alaikum Wr. Wb.